Expression of HGF and c-Met Proteins in Human Keratoconus Corneas. (30th November 2015) - You, Jingjing; Wen, Li; Roufas, Athena; Hodge, Chris; Sutton, Gerard; Madigan, Michele C.
Abstract : Keratoconus (KC) is a progressive degenerative inflammatory-related disease of the human cornea leading to decreased visual function. The pathogenesis of KC remains to be understood. Recent genetic studies indicate that gene variants of an inflammation-related molecule, hepatocyte growth factor ( HGF ), are associated with an increased susceptibility for developing KC. However HGF protein expression in KC has not been explored. In this initial study, we investigated late-stage KC and control corneas for the expression of HGF and its receptor mesenchymal-epithelial transition factor (c-Met/Met). KC buttons (~8 mm diameter) (n = 10 ) and whole control corneas (n = 6 ) were fixed in 10% formalin or 2% paraformaldehyde, paraffin embedded and sectioned. Sections were immunolabelled with HGF and c-Met antibodies, visualised using immunofluorescence, and examined with scanning laser confocal microscopy. Semiquantitative grading was used to compare HGF and c-Met immunostaining in KC and control corneas. Overall, KC corneas showed increased HGF and c-Met immunostaining compared to controls. KC corneal epithelium displayed heterogeneous moderate-to-strong immunoreactivity for HGF and c-Met, particularly in the basal epithelium adjacent to the cone area. Taken together with the recent genetic studies, our results further support a possible role for HGF/c-Met in the pathogenesis of KC.